Contemporary approaches to behaviour and mental health in the classroom : weaving together theory, practice, policy and educational discourse - Clarke, Emma (London: Routledge, 2022)
"Based on latest research in the field, this book links theory and practice with key agendas and policies on behaviour, children's mental health and well-being. It considers how policy and research influence and provides a range of whole-school and individual-teacher actions to support all children, but particularly for those whose behaviour is seen as challenging. Emma Clarke provides guidance on how practitioners should most effectively support children and manage pupils' behaviour and tracks how theory and policy has had a meaningful impact on what we do in the classroom. The book is divided into three distinct parts, each with its own set of reflective activities and thinking points as well as suggestions for further reading. Chapters in section one includes a focus on what informs the actions taken to support and manage behaviour in the classroom. In section two, the chapters move on to consider specific approaches and delve into the theories and research which underpin them. The final section shares ethos-focused approaches to supporting behaviour including the use of philosophical inquiry by Dr Aimee Quickfall, a timely and highly important review of the 'eternal verities' by Professor John Visser, and an overview of Finnish perspectives on behaviour in schools - a country often, and rightly, held up as a beacon on good practice. The book presents a range of research, policy and practice and, as such, aim to be of use to a range of readers. It can support and develop practitioners in the classroom, from early career teachers to those with a wealth of experience, as well as senior leaders and those working in wider contexts with children. It will also be useful for students and researchers due to the balance of theory and practice presented"--
Introduction to Book -- Section 1. Introduction: Framing the Actions We Take. Behaviour and Mental Health -- Acronyms and Attitudes -- School Policies: Possibilities and Problems -- Conclusion: Framing the Actions we Take -- Section 2. Introduction: Attitudes, Beliefs, and Perspectives. Theory and the Classroom -- Restorative Practice: Reconciliation and Restitution -- Solution Focused Working: Celebrating Success -- Conclusion: Attitudes, Beliefs and Perspectives -- Section 3. Introduction: Beyond Strategies to Embedded Ethos. Philosophical Inquiry -- Verities Revisited -- International Perspectives -- Conclusion: Beyond Strategies to Embedded Ethos -- Final Thoughts.
Includes bibliographical references and index.
Keywords: Classroom management; Students; School improvement programs; Teachers